Vaccine hesitancy and risk perception among health-care workers in a tertiary hospital in North-East India - Bishwalata Rajkumari; Avinash Keisam; Ningthoukhongjam Shugeta Devi; Samurailatpam Priyanka Devi; Regina Wahengbam; Mangvung Mangboi Haokip (Wolters Kluwer Medknow Publications, 2022)
Context: Vaccine hesitancy is an important threat to public health and a major setback for achieving herd immunity especially during the COVID 19 pandemic. Health-care workers are a major reckoning force in making the vaccines acceptable to the general population and the question is why there is vaccine hesitancy among them. Aims: The study plans to determine the reasons of vaccine hesitancy among health-care workers and to assess the association between their risk perception and variables of interest. Settings and Design: A cross-sectional study was conducted among doctors, nurses and other support staff in a tertiary hospital in North-East India, who were hesitant to take the vaccine when it was their turn. Methods and Material: Using convenience sampling method, data collection was done using a pre-tested interview schedule after obtaining informed verbal consent. Ethical clearance was obtained from the Institutional ethics committee. Statistical analysis used: Descriptive statistics like Mean, SD and percentages were used. Chi-square and Fisher's exact tests were used for association. Results: There were 160 participants out of which 30 (18.8%) had low risk perception of COVID-19 infection. Three (1.87 %) of the respondents said they were never going to be vaccinated against the disease and 59 (36.87%) said they may get the vaccine maybe at a later date. While 56 (35%) of the individuals were scared of common AEFI's like fever, chills and rigor; 21 (13.12%) were scared of unknown side effects. Fifteen percent of the respondents had trust issues with the vaccines. Conclusions: Though majority of the respondents had high-risk perception of COVID-19 infection, but almost one-sixth had trust issues with the vaccine. Trust building for the vaccine and information, education, and communication must be in the forefront for making the vaccination drive a success.